RESPON MASYARAKAT TERHADAP HADIRNYA IMIGRAN DI RUMAH DETENSI IMIGRASI PEKANBARU - Sihar Johansen Sitompul; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This script is titled " Society Response to The Presence of Immigrants at Pekanbaru Immigration Detention House". The research for this paper was conducted at Simpang Tiga,  Bukit Raya Subdistrict, Pekanbaru. The research itself focuses on the level of knowledge of the community about immigrants and the response of the community to the presence of immigrants around the Simpang Tiga area where the Immigration Detention Center is located on St. O.K.M Jamil precisely behind the Purna MTQ field, Pekanbaru. The researcher himself uses a sampling technique that is Simple Random Sampling because there are so many populations. The number of respondents in this study were 100 people taken from the Simpang Tiga community. The method used in this study is to use quantitative descriptive research methods because this method can calculate and describe the results of detailed responses through calculation of the score obtained in the study with the description. The instruments used in collecting data are observation, questionnaires, and documents. The theory used is response theory which describes the depiction of human stimulus in the face of stimulation. The results of the study itself illustrate that the Simpang Tiga community has a high knowledge base so that they can understand well about the definition of immigrants, the problems posed, the basis of immigration law, and also the institutions that handle it. But in terms of the level of response that is describing that the community there still treats the presence of immigrants there does not cause negative effects and affects lives, people still consider and behave naturally. However, the people remain vigilant and guard themselves against the possibility of immigrants who commit criminal and dangerous acts, especially terror threats. The level of security of the Pekanbaru Immigration Detention House which is still under control makes the community not too afraid of immigrants. Keywords: Society, Response, Immigrants